1985
DOI: 10.2307/357865
|View full text |Cite
|
Sign up to set email alerts
|

Self-Efficacy and Writing: A Different View of Self-Evaluation

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
92
0
4

Year Published

1993
1993
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 143 publications
(116 citation statements)
references
References 6 publications
12
92
0
4
Order By: Relevance
“…They then adapted the writing self-efficacy scale to study the fourth, seventh, and tenth graders and found that students' writing self-efficacy predicted their reading and writing achievement operationalized as mechanical skill and essay writing (Shell et al, 1995). Similar findings have been reported in other studies of writing self-efficacy and writing achievement (McCarthy, Meier, & Rinderer, 1985;Pajares & Johnson, 1996;Pajares & Valiante, 1997. Given the positive impact that writing self-efficacy has on writing achievement stated in the literature, this study used a self-efficacy scale that specifically measures students' confidence in their ability to write English paragraphs (see items in Appendix A).…”
Section: Goal Orientationsupporting
confidence: 65%
“…They then adapted the writing self-efficacy scale to study the fourth, seventh, and tenth graders and found that students' writing self-efficacy predicted their reading and writing achievement operationalized as mechanical skill and essay writing (Shell et al, 1995). Similar findings have been reported in other studies of writing self-efficacy and writing achievement (McCarthy, Meier, & Rinderer, 1985;Pajares & Johnson, 1996;Pajares & Valiante, 1997. Given the positive impact that writing self-efficacy has on writing achievement stated in the literature, this study used a self-efficacy scale that specifically measures students' confidence in their ability to write English paragraphs (see items in Appendix A).…”
Section: Goal Orientationsupporting
confidence: 65%
“…One of the research foci of these studies is writing self-efficacy and its ties to several writing-related variables, such as use of writing strategies, writing anxiety, and writing performance (Erkan & Saban, 2011;Sanders-Reio et al, 2014). Previous studies have shown that students with high writing self-efficacy tend to write better and have lower writing anxiety than those with low writing self-efficacy (McCarthy, Meier, & Rinderer, 1985;Pajares & Valiante, 2006). More recently, writing self-efficacy has also been found to be a more significant predictor of students' writing performance than writing anxiety (Sander-Reio et al, 2014;Woodrow, 2011).…”
Section: Research On Writing Self-efficacymentioning
confidence: 99%
“…Consequently, there is lack of research which has thoroughly and scientifically delved into the developmental or achievement-level differences in children's beliefs about writing to date. According to the survey of some studies, the beliefs of adult and skilled participants are less strongly associated with achievement for writing (McCarthy et al, 1985;Shell et al, 1989); however, how this difference in the strength of the relation for writing develops and whether this difference also occurs for persons at other achievement levels presently are not known.…”
Section: Developmental Stages Of Self-efficacymentioning
confidence: 99%